2017
DOI: 10.1002/acn3.418
|View full text |Cite
|
Sign up to set email alerts
|

CNS Aquaporin‐4‐specific B cells connect with multiple B‐cell compartments in neuromyelitis optica spectrum disorder

Abstract: ObjectivesNeuromyelitis optica spectrum disorder (NMOSD) is a severe inflammatory disorder of the central nervous system (CNS) targeted against aquaporin‐4 (AQP4). The origin and trafficking of AQP4‐specific B cells in NMOSD remains unknown.MethodsPeripheral (n = 7) and splenic B cells (n = 1) recovered from seven NMOSD patients were sorted into plasmablasts, naïve, memory, and CD27‐IgD‐ double negative (DN) B cells, and variable heavy chain (VH) transcriptome sequences were generated by deep sequencing. Perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 34 publications
5
60
0
Order By: Relevance
“…Yet, these observations appear different to the more limited intrathecal expansions observed in neuromyelitis optica spectrum disorder and the very low mutational load in CSF B cells from patients with NMDA receptor (NMDAR) antibody encephalitis. 14,15 Hence, it may be that several different immunologic mechanisms operate across these autoantibodymediated conditions. Our study did not aim to examine the antigen-specific population or correlate intrathecal B-cell responses with clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these observations appear different to the more limited intrathecal expansions observed in neuromyelitis optica spectrum disorder and the very low mutational load in CSF B cells from patients with NMDA receptor (NMDAR) antibody encephalitis. 14,15 Hence, it may be that several different immunologic mechanisms operate across these autoantibodymediated conditions. Our study did not aim to examine the antigen-specific population or correlate intrathecal B-cell responses with clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…CD19 + CD20 + and CD19 + CD20 low B cell subsets (Suppl. Figure 2) were first selected from other cell populations as previously described [15]. Naïve B cells (CD19 + CD20 + IgD + CD27 − ) and memory B cells (CD19 + CD20 + CD27 + ) were further separated from the CD19 + CD20 + population,…”
Section: Standard Protocol Approvals Registrations and Patientsmentioning
confidence: 99%
“…These sequences can be compared to those derived from a proteomic analysis of the serum autoantibody repertoire within the same patient. This approach has been performed in several studies which have shown close associations between the B cell and the immunoglobulin repertoire (76) and others that point toward more diversity in the serum immunoglobulins (77). Three of the MuSK mAbs demonstrated pathogenic capacity in the AChR clustering assay.…”
Section: Limitationsmentioning
confidence: 99%